INOVASI PELAYANAN PT. POS INDONESIA DALAM MENGHADAPI PERSAINGAN JASA PENGIRIMAN UANG (STUDI KASUS PT. POS INDONESIA DI PEKANBARU) - Valentyna D L, Chris; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
the modern world, innovationis amajor challenge forany organization. The aim of the research is to get and to seen the information about innovation PT. Pos Indonesia to confront the competition services of transfering money in Pekanbaru city. With seeing so much competitor in transfering money in Pekanbaru city, researcher want to know the strategy PT. Pos Indonesia infacing the competition of transfering money in Pekanbaru city.Theory used in this study was the Inovation by Basuki (2013:179) and theory of SWOT analysis (Rangkuti 2009:33). This study uses qualitative research methods to study descriptive data. In data collection, and with SWOT analysis to analysing data, researcher using observation, interviews, documentation.Based on the result of the research through interviews and observations, it is known that inovation PT. Pos Indonesia in facing the competition of transfering money in eklanbaru city still hampered with some case like apromotion of a product that should be interasting and public know what kind of product that PT. Pos Indonesia give to them, and public want to use that product. PT. Pos Indonesia weak with analysing a new product that competitor gives to public. Then, PT. Pos Indonesia is not use well their strengths and can’t maximize well their oppurtunities.Keyword: Innovation Strategy, Public Service.